2008
DOI: 10.1007/s10750-008-9376-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increases in salinity on phytoplankton in the Broadwater of the Myall Lakes, NSW, Australia

Abstract: The Broadwater of the Myall Lakes system is highly susceptible to cyanobacterial bloom formation after heavy rain events. During prolonged low flow periods, saline intrusion from the lower Myall River increases salinity levels and effectively controls some bloom forming algal taxa. To assess the effect of low-to-moderate increases in salinity (up to 4 ppt) on phytoplankton chlorophyll a, cell abundance, diversity and assemblage structure, salinity enhancement experiments were conducted on Broadwater samples co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…6, CCA) whereas DIN:DIP added little to the explained variability. This confirms a suggestion made by Redden and Rukminasari (2008), that enriched treatments of different DIN:DIP ratios do not lead to different taxonomic diversity, however, different salinity treatments result in variations in taxonomic diversity. In our study, an increase in salinity had a stronger effect on the algal community composition than nutrients (N and P).…”
Section: Discussionsupporting
confidence: 90%
“…6, CCA) whereas DIN:DIP added little to the explained variability. This confirms a suggestion made by Redden and Rukminasari (2008), that enriched treatments of different DIN:DIP ratios do not lead to different taxonomic diversity, however, different salinity treatments result in variations in taxonomic diversity. In our study, an increase in salinity had a stronger effect on the algal community composition than nutrients (N and P).…”
Section: Discussionsupporting
confidence: 90%
“…Only a few eukaryotic taxa, including the chlorophyte genera Oocystis and Cosmarium, the diatom Thalassiosira and the dinoflagellate Gymondinium, tended to persist above an electrical conductivity of 5 mS cm -1 , although at reduced abundances. Redden & Rukminasari (2008) also report a reduction in chlorophyte abundance in Bombah Broadwater phytoplankton communities after salinity was increased from 4 to 8 g l -1 . Salinity has been used to explain the greatest variation in diatom species composition and abundance in the Murray River (Tibby & Reid, 2004), and negative correlations between salinity and diatom richness have been shown for Victorian and West Australian inland waters (Blinn & Bailey, 2001;Blinn et al, 2004).…”
Section: Discussionmentioning
confidence: 77%
“…Winder & Cheng (1995) found that salinities of 5-7 g l -1 (7-10 mS cm -1 ) inhibited the growth of Anabaena circinalis, whilst Otsuka et al (1999) reported net growth of Microcystis aeruginosa at salinities up to 7 g l -1 or about 10 mS cm -1 . Redden & Rukminasari (2008) also found that Anabaena circinalis from Bombah Broadwater were negatively affected by increased salinity. Only a few eukaryotic taxa, including the chlorophyte genera Oocystis and Cosmarium, the diatom Thalassiosira and the dinoflagellate Gymondinium, tended to persist above an electrical conductivity of 5 mS cm -1 , although at reduced abundances.…”
Section: Discussionmentioning
confidence: 87%
“…Anabaena occurs both in freshwater and brackish water, but in our study the growth of Anabaena was higher in Reposaari, the freshwater area. Redden and Rukminasari (2008) showed that a slight increase in salinity (2%) had a strong negative effect on cell numbers of Anabaena. The differences between sites highlight the importance of repeating experiments in different locations in order to make general conclusions.…”
Section: Growth Conditionsmentioning
confidence: 99%